Brand Awareness, Brand Association, Perceived Quality, Dan Pengaruhnya Terhadap Loyalitas Pelanggan Susu Ultra Milk (Studi Kasus di Indogrosir Kota Malang) - Desti Ikromah; Nur Hidayati; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted to determine Brand Awareness, Brand Association, Perceived Quality and Influence on Customer Loyalty of Ultra Milk (Case Study in Indogrosir Malang City). This research belongs to the type of explanatory research with a quantitative approach, which was conducted to examine the effect between variables. The population in this study were customers of ultramilk milk in Indogrosir Malang City. From this population a sample will be determined using the formula method from Malhotra so that a sample of 85 samples is obtained. Data analysis in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test. The results of this study indicate that based on the results of the t test and f test, there is a simultaneous influence between brand awareness, brand association, and perceived quality variables on the customer loyalty variable for ultramilk milk (Case study in Indogrosir Malang City). Adjusted R Square of 62.1% to the dependent variable, namely customer loyalty can be explained by the variable brand awareness (X1), brand association (X2), perceived quality (X3) while 37.9% is explained by other variables outside the research model. Keyword: costumer Loyalty, Brand Awareness, Brand Association, Perceived Quality